2010
DOI: 10.17221/90/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell quality and calcium utilization in feed of hens in repeated laying cycles

Abstract: Hens of the laying hybrid Shaver Starcross 288 were used in two consequential experiments. The first experiment (for 10 months) was conducted on hens at the age from 18 to 60 weeks (1<sup>st</sup> cycle; <i>n</i> = 50) and moulted hens after 10 months laying from 70 to 110 weeks of age (2<sup>nd</sup> cycle; <i>n</i> = 50). For the second experiment (for 8 months) in the 1<sup>st</sup> cycle 18 weeks old hens were bought (<i>n</i> = 60) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
(25 reference statements)
0
9
1
3
Order By: Relevance
“…However, there was a significant interaction (P ≤ 0.050) between temperature and age -higher shell percentage was measured in old birds at 20°C (11.7%) but the lowest also in old hens but at 28°C (10.8%). Specific gravity was higher (P ≤ 0.001) in laying hens, and decreased (P ≤ 0.029) with age, which differed from the results of Arpášová et al (2010) where no relationship between specific gravity and age was found. Specific gravity was also reduced (P ≤ 0.007) by temperature, which was frequently reported in the past, e.g.…”
Section: Resultscontrasting
confidence: 92%
“…However, there was a significant interaction (P ≤ 0.050) between temperature and age -higher shell percentage was measured in old birds at 20°C (11.7%) but the lowest also in old hens but at 28°C (10.8%). Specific gravity was higher (P ≤ 0.001) in laying hens, and decreased (P ≤ 0.029) with age, which differed from the results of Arpášová et al (2010) where no relationship between specific gravity and age was found. Specific gravity was also reduced (P ≤ 0.007) by temperature, which was frequently reported in the past, e.g.…”
Section: Resultscontrasting
confidence: 92%
“…The dynamics of changes in the eggshell properties in hens are related to physiological processes of mineral metabolism before, during, and after molting. During the pre-laying period, young hens create reserves of mineral substances especially calcium, which is stored in bones and other tissues [14]. However, during the laying period, the Ca reserves in medullar bones reduce, and an insufficient intake of Ca through the feed, the eggshell quality deteriorates, the incidence of nonstandard and broken eggs increased, and also shell-less eggs can be laid [14].…”
Section: Resultsmentioning
confidence: 99%
“…During the pre-laying period, young hens create reserves of mineral substances especially calcium, which is stored in bones and other tissues [14]. However, during the laying period, the Ca reserves in medullar bones reduce, and an insufficient intake of Ca through the feed, the eggshell quality deteriorates, the incidence of nonstandard and broken eggs increased, and also shell-less eggs can be laid [14]. Moreover, it is worth mentioning that dark-colored eggshells contain a higher percentage of CaCO 3 when compared to white-colored eggshells and this may be due erence in hens' diet [15], indicating that brown egg has a higher strength than a white one.…”
Section: Resultsmentioning
confidence: 99%
“…According to Adil et al (2010), organic acids are able to increase the digestibility of calcium, phosphorus, magnesium, zinc, and proteins. The availability of calcium is the main factor that determines the eggshell quality because calcium mineral is the major component of the eggshell (Arpášová et al, 2010;Shwetha et al, 2018). Asam kandis contains hydroxy citric acid (Onakpoya et al, 2011) that might be able to enhance calcium absorption and decrease calcium excretion by acid-base balance mechanism in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%